Stimulasi Kemampuan Motorik Halus Anak Usia 5-6 Tahun Melalui Kegiatan Membuat Alat Permainan Edukatif - Ni Ketut Suarmini; I Wayan Suyanta; Ida Bagus Komang Sindu Putra (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Early childhood is a unique individual who needs to given learning differently from children over their age. Early childhood learning is presented through playing or making toys. Through activity of making toys make children have good knowledge without them knowing it. Activities to make APE can stimulate various aspects of children's abilities. Fine motor abilities are one of aspects that cannot missed in the provision of stimulus. Purpose of this study is explore effective learning activities to stimulate fine motor skills of early childhood age 5-6 years in TK Negeri Pembina Abiansemal. This research was carried out using qualitative descriptive research methods. Results showed effective learning was carried out using interesting and fun learning methods. Obstacles experienced by teachers in developing stimulation of fine motor skills are factors from inside and outside the child. Impact of stimulating fine motor abilities of children aged 5-6 years through activity of making educational game tools shows positive and negative impacts. Data obtained, seen that positive impact more than negative impact so that stimulation provided also better. Teachers have tried resolve negative impact so this learning method can continue to be applied.